A Comprehensive Comparison of Different Selenium Supplements: Mitigation of Heat Stress and Exercise Fatigue-Induced Liver Injury - Chen, Xinwei; Zhang, Jian; Li, He; Liu, Wanlu; Xi, Yu; Liu, Xinqi (Frontiers in Nutrition, 2022)
This study aimed to compare the protective effects of different selenium supplements against heat stress and exercise fatigue-induced liver injury and to investigate the potential mechanisms of action. The selenium-riched soybean peptides (SePPs) with higher hydrolysis degree and selenium retention were isolated via alkaline solubilization and acid precipitation and the enzymatic hydrolysis of alkaline protease, neutral protease, and papain. The results showed that SePPs could significantly increase the antioxidant levels in rats, inhibit lipid peroxidation, and reduce liver enzyme levels in rat serum, while the histological findings indicated that the inflammatory cell infiltration in the liver tissue was reduced, and new cells appeared after treatment with SePPs. SePPs can also increase glutathione (GSH) and GSH peroxidase (GSH-Px) in the liver, as well as protect the liver by regulating the NF-κB/IκB pathway, preventing interleukin 1β (IL-1β), interleukin 6 (IL-6), and tumor necrosis factor α (TNF-α) release in the liver. The SePPs displayed higher antioxidant and anti-inflammatory activity in vivo than selenium-enriched soybean protein (SePro), selenomethionine (SeMet), sodium selenite (Na2SeO3), and common peptides (PPs). These findings suggest that SePPs can be used as a priority selenium resource to develop heatstroke prevention products or nutritional supplements.